Przestrzeń zabaw ryzykownych w przedszkolu leśnym - Patrycja Brudzińska (Problemy Wczesnej Edukacji)
The subject of the qualitative research presented in this paper is risky play. Using the conclusions of the participant observation carried out in two forest kindergartens in Berlin, interviews with teachers and the analysis of documents, I try to answer the question of what factors are conducive to taking up risky play by children. I present the types of risky play that occur in forest kindergarten and a description of the material and social space that characterizes the institutions. The key issue in recognition is the teachers’ attitude to risky play. Children learn to manage risk, make decisions, solve problems, assess their own physical fitness, but taking such actions requires appropriate suport from adults.